2017
DOI: 10.4103/sni.sni_49_17
|View full text |Cite
|
Sign up to set email alerts
|

More risks and complications for elective spine surgery in morbidly obese patients

Abstract: Background:The vast majority of studies emphasize the greater morbidity/mortality for elective spine surgery in morbidly obese patients.Methods:This review focuses on the increased morbidity/mortality of performing elective spinal operations in morbidly obese patients. There are two definitions of morbid obesity; a body mass index (BMI) of equal to or greater than 35 plus two major comorbid factors (e.g., hypertension, diabetes, etc.) or a BMI (morbidly obese III) of =≥40 kg/m2.Results:For patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
2
41
1
Order By: Relevance
“…20 Degenerative scoliosis, excessive body weight, and number of spinal levels involved are also notable risk factors for reoperation. 21,22 Intraoperative blood loss, combined comorbidities, 23 and preoperative hemoglobin level are possible risk factors according to previous studies. 24,25 Our study showed a strong relationship between the number of diseased segments and time to re-surgery; however, age and sex were not significant risk factors in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…20 Degenerative scoliosis, excessive body weight, and number of spinal levels involved are also notable risk factors for reoperation. 21,22 Intraoperative blood loss, combined comorbidities, 23 and preoperative hemoglobin level are possible risk factors according to previous studies. 24,25 Our study showed a strong relationship between the number of diseased segments and time to re-surgery; however, age and sex were not significant risk factors in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Within the general spine literature, obesity has been widely associated with increased complication incidence. [34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection.…”
Section: Discussionmentioning
confidence: 99%
“…9 Across a wide spectrum of surgical procedures, obesity has been shown to be a risk factor for surgical complications, including delayed wound healing and wound failure, surgical site infection, and postoperative venous thromboembolic events (VTEs). 1012 Although there have been few studies specifically examining obesity as a risk factor for surgical complications following gender-affirming vaginoplasty, some centers and surgeons employ BMI as a selection criteria for surgical candidacy, 13 denying vaginoplasty to patients with BMIs over an arbitrary cutoff (usually 30 or 35). 13…”
Section: Introductionmentioning
confidence: 99%